Retrospective evaluation of the Dutch pre‐newborn screening cohort for propionic acidemia and isolated methylmalonic acidemia: What to aim, expect, and evaluate from newborn screening?. Issue 3 (22nd December 2019) - Haijes, Hanneke A.; Molema, Femke; Langeveld, Mirjam; Janssen, Mirian C.; Bosch, Annet M.; van Spronsen, Francjan; Mulder, Margot F.; Verhoeven‐Duif, Nanda M.; Jans, Judith J.M.; van der Ploeg, Ans T.; Wagenmakers, Margreet A.; Rubio‐Gozalbo, M. Estela; et al.
Abstract: Evidence for effectiveness of newborn screening (NBS) for propionic acidemia (PA) and isolated methylmalonic acidemia (MMA) is scarce. Prior to implementation in the Netherlands, we aim to estimate the expected health gain of NBS for PA and MMA. In this national retrospective cohort study, the clinical course of 76/83 Dutch PA and MMA patients, diagnosed between January 1979 and July 2019, was evaluated. Five clinical outcome parameters were defined: adverse outcome of the first symptomatic phase, frequency of acute metabolic decompensations (AMD), cognitive function, mitochondrial complications, and treatment‐related complications. Outcomes of patients identified by family testing were compared with the outcomes of their index siblings. An adverse outcome due to the first symptomatic phase was recorded in 46% of the clinically diagnosed patients. Outcome of the first symptomatic phase was similar in 5/9 sibling pairs and better in 4/9 pairs. Based on the day of diagnosis of the clinically diagnosed patients and sibling pair analysis, a preliminary estimated reduction of adverse outcome due to the first symptomatic phase from 46% to 36%‐38% was calculated. Among the sibling pairs, AMD frequency, cognitive function, mitochondrial, and treatment‐related complications were comparable. These results suggest that the health gain of NBS for PA and MMA in overall outcome may be limited, as only a modest decrease of adverse outcomes due to the first symptomatic phase is expected. With current clinical practice, no reduced AMD frequency, improved cognitive function, or reduced frequency of mitochondrial or treatment‐related complications can be expected.